Three-Dimensional Fluid-Structure Interaction Case Study on Elastic Beam - Tabatabaei Malazi, Mahdi; Eren, Emir Taha; Luo, Jing; Mi, Shuo; Temir, Galip (MDPI, 2020)
A three-dimensional T-shaped flexible beam deformation was investigated using model experiments and numerical simulations. In the experiment, a beam was placed in a recirculating water channel with a steady uniform flow in the inlet. A high-speed camera system (HSC) was utilized to record the T-shaped flexible beam deformation in the cross-flow direction. In addition, a two-way fluid-structure interaction (FSI) numerical method was employed to simulate the deformation of the T-shaped flexible beam. A system coupling was used for conjoining the fluid and solid domain. The dynamic mesh method was used for recreating the mesh. After the validation of the three-dimensional numerical T-shaped flexible solid beam with the HSC results, deformation and stress were calculated for different Reynolds numbers. This study exhibited that the deformation of the T-shaped flexible beam increases by nearly 90% when the velocity is changed from 0.25 to 0.35 m/s, whereas deformation of the T-shaped flexible beam decreases by nearly 63% when the velocity is varied from 0.25 to 0.15 m/s.
Keywords: fluid-structure interaction; flexible beam; high speed imaging; system coupling; IMMERSED BOUNDARY METHOD; Engineering; Oceanography